Older adults’ emotional reactions to elder abuse: Individual and victimisation determinants - Santos, Ana João (2020)
Elder abuse has been gaining public, state, and scientific attention for the past 40 years, but research focusing on emotional reactions of older adults to victimisation is still scarce. The study describes the emotions and feelings of older adults who experienced abuse in a community setting, and the association between these emotions and individual or abuse characteristics. The cross‐sectional study comprises 510 older adults who were identified and referred by four institutions. Participants answered a questionnaire on elder abuse experiences, including the emotion or feeling brought out by the act of abuse that was perceived to be the most serious. Fear and sadness comprised 67.1% of all provided responses. Emotional reactions were associated with functional status, the presence of depressive symptoms, relationship with the perpetrator and, to a limited degree, to the experience of multiple types of abuse. The most significant and meaningful variable was the relationship with the perpetrator. This study demonstrates that older adults present very similar patterns of emotional reactions, but individual characteristics and the established relationship with the perpetrator might mediate the emotional response. Implications for prevention and intervention of elder abuse are discussed.